1942
DOI: 10.1017/s0305004100021976
|View full text |Cite
|
Sign up to set email alerts
|

The influence of radiation damping on the scattering of mesons

Abstract: I. It is shown that a general argument can be given for omitting the diverging parts of any quantized field interacting with a particle. The field equations thus freed from all singularities still contain the reaction of the field on the particle to the same extent as the reaction can be derived classically from the conservation of energy. The new field equations can be solved generally in terms of a simultaneous set of integral equations and do not give rise to any fundamental difficulties whatsoever.II. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1944
1944
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 11 publications
(3 reference statements)
0
8
0
2
Order By: Relevance
“…There seems little doubt now th a t these results are all due to multiple processes involving the production of mesotron showers. Heitler & Peng (1942) have shown th a t the probabilities of the production of showers of two or more mesotrons by a prim ary mesotron reach a maximum for certain definite values of the energy of the prim ary mesotrons; these values of the energy required to produce a maximum for showers of n particles increasing with n. The existence of mesotron showers has now been demonstrated by several ex periments. Schein, Jesse &Wollan (1941), andCarlson &Schein (1941) The mesotrons composing such showers will give rise to fast electrons a t some point in their path, and these fast electrons will in tu rn produce by the usual cascade process the electron showers which are observed as bursts under large thicknesses.…”
Section: Discussionmentioning
confidence: 88%
“…There seems little doubt now th a t these results are all due to multiple processes involving the production of mesotron showers. Heitler & Peng (1942) have shown th a t the probabilities of the production of showers of two or more mesotrons by a prim ary mesotron reach a maximum for certain definite values of the energy of the prim ary mesotrons; these values of the energy required to produce a maximum for showers of n particles increasing with n. The existence of mesotron showers has now been demonstrated by several ex periments. Schein, Jesse &Wollan (1941), andCarlson &Schein (1941) The mesotrons composing such showers will give rise to fast electrons a t some point in their path, and these fast electrons will in tu rn produce by the usual cascade process the electron showers which are observed as bursts under large thicknesses.…”
Section: Discussionmentioning
confidence: 88%
“…In that case 0.158 GeV would be the 'temperature' at which the two nucleons were emitted. 6 It thus seemed that there was something statistical, a suspicion strangely corroborated by the observation that the same law (with slightly different 'temperature') was obeyed by secondaries in inelastic processes [36]. Almost 2 years before the Orear plot was published, L.W.…”
Section: The Decisive Turn Of the Screw: Large-angle Elastic Scatteringmentioning
confidence: 98%
“…The only field theory then known, quantum electrodynamics (as yet without a consistent renormalization scheme), suggested that events with many secondaries should have vanishingly small cross-sections [proportional to .e 2 / n ]. This led many theoreticians to the interpretation that such events must be the result of many interactions with different nucleons in the same heavy nucleus, each single interaction producing just one pair, a point of view [5][6][7] persisting even after the advent of meson theory and in spite of growing experimental evidence in favour of multiple production. Heisenberg-still unaware of Yukawa's paper-was the first to claim that, in a single elementary interaction, many secondaries might be produced [8], which at that time was a heretical idea-the pion was discovered 11 years later!…”
Section: Multiple Production: Heisenberg (1936)mentioning
confidence: 99%
See 1 more Smart Citation
“…Le sixième paragraphe comporte essentiellement une mise au point de l'équation de Heitler Peng [5], [6] modifiée par Gora-Paul [8] : la déduction que nous présentons nous semble intuitive dans son souci de séparer les transitions intérieures à une certaine couche d'énergie des transitions , extérieures à cette couche. Ceci revient à séparer Article published online by EDP Sciences and available at http://dx.doi.org/10.1051/jphysrad:019530014011059100 l'espace de Hilbert des vecteurs d'état considérés en deux sous-espaces complémentaires, l'équation en question s'obtenant quand on élimine entre certaines équations valant chacune dans son sousespace des grandeurs extérieures à la couche consi-dérée.…”
unclassified